Improved clinical outcomes after revision arthroplasty with a hinged implant for severely stiff total knee arthroplasty - van Rensch, Paul J. H. (Knee Surg Sports Traumatol Arthrosc, 2018)
PURPOSE: Management of the severely stiff total knee arthroplasty (TKA) is challenging, with the outcome of revision arthroplasty being inferior compared to the outcome for other indications. The aim of this study was to analyse the outcome after revision TKA with hinged-type implants for severely stiff TKA [range of motion (ROM) ≤ 70°] at 2 years. METHODS: A cohort of 38 patients with a hinged-type revision TKA (Waldemar Link or RT-Plus) and preoperative ROM ≤ 70° were selected from a prospectively collected database. ROM, visual analogue scale (VAS) for pain and satisfaction and Knee Society Score (KSS) were obtained preoperatively and at 3 months, 1 year and 2 years. Pre- and postoperative outcome were compared at 2 years. RESULTS: There was a significant increase in ROM and KSS. VAS pain scores did not differ significantly. The median ROM at 2 years was 90° (range 50°–125°) with a median gain of 45° (range 5°–105°). Median VAS pain was 28.5 (range 0–96) points and median VAS satisfaction was 72 (range 0–100) points at 2 years. Twelve patients suffered a complication. Recurrent stiff knee was the most frequently reported complication (n = 5). CONCLUSIONS: Hinged-type revision TKA following a severely stiff TKA renders a significant, although moderate, clinical improvement at 2 years. LEVEL OF EVIDENCE: Retrospective case series. Level IV.